Digital Entrepreneurship Model: Optimizing Internal and External Support for Female Entrepreneurs - Nungky Viana Feranita; Alifian Rizzalul Ahmad; Ahmad Rizky Hasan (Integrated Journal of Business and Economics (IJBE), 2023)
Female entrepreneurs experienced a decline in performance during the Covid-19 pandemic. To overcome the impact of this pandemic, entrepreneurs are adopting digital technology. However, female entrepreneurs continue to face obstacles both internal (family, finance, knowledge) and external (community, business partners, government). This study aims to find digital entrepreneurship models for female entrepreneurs. The target of this research is to find out the factors that can affect the performance of female entrepreneurs, especially the role of digital technology adoption as a moderating variable between internal and external support relationships and the level of entrepreneurship. This research was conducted in Jember Regency. The unit of analysis is the organization represented by female entrepreneurs who have adopted digital technology. This study uses a quantitative approach with survey method. Data analysis using PLS-SEM analysis. The results showed that internal and external support had a significant effect on the level of entrepreneurship. The level of entrepreneurship has a significant effect on the performance of female entrepreneurs. Adoption of digital technology deserves to be a moderating variable that strengthens the relationship between external support and the level of entrepreneurship. Meanwhile, the relationship between internal support and the level of entrepreneurship is not affected by the adoption of digital technology.